ROS‐Responsive Camptothecin Prodrug Nanoparticles for On‐Demand Drug Release and Combination of Chemotherapy and Photodynamic Therapy. (20th September 2020) - Chu, Bingyang; Qu, Ying; He, Xinlong; Hao, Ying; Yang, Chengli; Yang, Yun; Hu, Danrong; Wang, Fangfang; Qian, Zhiyong
Abstract: Minimizing drug leakage in systemic circulation, synchronizing the in vivo fate of multiple drugs, and precisely controlling tumor locoregional drug release, remain challenging for nanomedicine‐based cancer therapy. Here, a reactive oxygen species (ROS)‐responsive camptothecin (CPT) prodrug delivery system (MPEG‐(TK‐CPT)‐PPa) is developed, in which CPT and photosensitizer pyropheophorbide‐a (PPa) are concurrently conjugated to the same poly(ethylene glycol) methyl ether (MPEG) via ROS‐responsive thioketal (TK) and lipid linkage. The synthesized MPEG‐(TK‐CPT)‐PPa conjugate self‐assembles to form nanoparticles (NPs) (43.6 ± 0.8 nm) in solution. The covalently conjugated prodrug prevents drug leakage during systemic circulation and synchronizes the in vivo distribution of the two drugs. The generated fluorescence signal of PPa helps precisely track and locate the NPs at tumor sites. Under the guidance of imaging, a near‐infrared laser locally irradiates tumor tissue upon reaching the strongest fluorescence. The ROS generated by PPa not only cleaves the TK linkage and then triggers locoregional, controllable and on‐demand CPT release, but also exhibits cytotoxic effects on tumor cells. Thus, CPT‐mediated chemotherapy and PPa‐induced photodynamic therapy lead to the combined and enhanced suppression of tumor growth. Accordingly, such laser‐triggered, localized, controllable, and on‐demand drug release systems may provide an alternative option for CPT formulations. Abstract : A reactive oxygen species (ROS)‐responsive camptothecin (CPT) prodrug system with the covalently conjugated CPT and pyropheophorbide‐a (PPa) is developed to reduce the toxicity and synchronize the in vivo fate of two drugs. The generated ROS by PPa under laser irradiation not only triggers on‐demand release of CPT, but also enables photodynamic therapy.